Is the transition over? - Oleh Havrylyshyn (Queen's University, Department of Economics, 2009)
While many observers thought it was premature for Czech Prime Minister Klaus to suggest in 1995 the transition was over except for fine-tuning , as we approach the 20th year after the fall of the Berlin Wall on Nov. 9, 1989,-and the 18th after the dissolution of the Soviet Union at Byelovezha- it is surely relevant to ask the question again. The first new contribution of this paper is to show that ,for all practical purposes, the post-communist transition is over in eight or nine early reformers of Central Europe and the Baltics; but it is not over for other transition countries -though many are close, and only a few very far behind. The second and perhaps more important novelty of this paper is that it goes beyond the qualitative expert judgments in earlier studies addressing this question. With one or two exceptions, earlier studies did not start with an explicit analytical definition of transition and its end-point, and evidence provided was selective often mixing partial quantitative measures with qualitative judgments-albeit well reasoned ones. This paper proposes an analytical definition of transition and its end-point , as well as ways this can be measured quantitatively without undertaking impossibly massive econometric exercises .
Keywords: F15; N10; N14; O11; P02; 330; transition; efficient allocation; share of consumption; share of industry; direction of trade; trade openness; comparative advantage; Systemtransformation; Wirtschaftliche Anpassung; Transformationsstaaten